STAYCATION SEBAGAI WISATA ALTERNATIF MASA PANDEMI COVID-19 - Ni Luh Christine Prawitha Sari Suyasa; Putu Chris Susanto; Agus Satyananda M (UHN IGB Sugriwa Denpasar, 2022)
Restrictions on tourist mobility during the Covid-19 Pandemic led to a change in vacation trends, from Vacation to Staycation. The local community out of 255 respondents living in Badung Regency is familiar witho the word Staycation. 62.2% have done a staycation on both